The Parasitic Fingerprint: Tracing Infection to Host Illness - Shubham Sah; Deepa Kumari (Recent Trends in Infectious Diseases, 2026)
Parasitic infections remain a major global health burden, causing significant morbidity and mortality, particularly in tropical and subtropical regions. A critical aspect of disease pathogenesis is the unique molecular and cellular imprint left by parasites in their hosts, termed the “parasitic fingerprint.” These fingerprints encompass parasite-derived proteins, nucleic acids, metabolites, extracellular vesicles, and host responses, including gene expression changes, cytokine profiles, and metabolic adaptations. Advances in multi-omics technologies, which integrate genomics, transcriptomics, proteomics, metabolomics, and epigenomics, have enabled high-resolution mapping of host–parasite interactions, revealing strategies parasites employ to invade, survive, and manipulate host systems. Molecular fingerprints offer clinical relevance by providing sensitive diagnostic markers, informing disease prognosis, guiding vaccine design, and enabling targeted therapeutic interventions. Case studies in malaria, leishmaniasis, trypanosomiasis, and helminth infections demonstrate the utility of fingerprints in linking parasite activity to tissue-specific pathology and host immune modulation. Integration of these insights into emerging technologies, such as single-cell multi-omics, spatial transcriptomics, and artificial intelligence, holds promise for personalized medicine approaches, improving disease management and reducing the global burden of parasitic diseases.
Keywords: Diagnostics; Malaria; Parasitic fingerprint; Precision medicine; helminths; host-parasite interactions; leishmaniasis; multi-omics; therapeutics; trypanosomiasis